2020
DOI: 10.1007/s10433-020-00590-7
|View full text |Cite
|
Sign up to set email alerts
|

Do older manual workers benefit in vitality after retirement? Findings from a 3-year follow-up panel study

Abstract: Vitality is the feeling of physical and mental aliveness. Vitality benefits individual, organizational and societal well-being. However, we know much less about the dynamics in the levels of vitality and its’ precursors. This study investigates the effects of retirement on vitality and how this effect differs between manual and non-manual workers and by baseline levels of vitality. We used two waves of the NIDI Pension Panel Survey, collected in the Netherlands in 2015 and 2018. Data from 4156 older workers (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, we controlled for two work-related variables: manual work and employment status. Manual work has been associated with lower vitality, higher physical job demands and higher physical health impairments ( Mutambudzi & Henkens, 2021 ; Schaufeli & Taris, 2014 ; Vanajan, Bültmann, & Henkens, 2021 ). Past research has also shown differences in healthy life expectancy between older adults in high and low occupational positions ( Head et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we controlled for two work-related variables: manual work and employment status. Manual work has been associated with lower vitality, higher physical job demands and higher physical health impairments ( Mutambudzi & Henkens, 2021 ; Schaufeli & Taris, 2014 ; Vanajan, Bültmann, & Henkens, 2021 ). Past research has also shown differences in healthy life expectancy between older adults in high and low occupational positions ( Head et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this large-scale, time-lagged NPPS data collection is to understand retirement-eligible workers’ transition from work to retirement in the Netherlands (Henkens et al, 2017). Several studies were published using the two-wave NPPS data (see https://nidi.nl/en/publications, for a comprehensive publication list; e.g., Grünwald et al, 2021, 2022; Vanajan et al, 2021, 2022; van Solinge et al, 2022). This data set has a multilevel design, in which older workers are nested within organizations, offering opportunities to examine the roles of organization-level climates in retirement-eligible workers’ retention decisions.…”
Section: Studymentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. Grünwald et al, 2021Grünwald et al, , 2022Vanajan et al, 2021Vanajan et al, , 2022van Solinge et al, 2022). This data set has a multilevel design, in which older workers are nested within organizations, offering opportunities to examine the roles of organization-level climates in retirementeligible workers' retention decisions.…”
Section: Study 1 Samplementioning
confidence: 99%